2004
DOI: 10.1007/s10055-004-0134-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and display of enhancing information in desktop information-rich virtual environments: challenges and techniques

Abstract: Abstract:Information-Rich Virtual Environments (IRVEs) have been described as environments in which perceptual information is enhanced with abstract (or symbolic) information such as text, numbers, images, audio, video, or hyperlinked resources. Desktop VE applications present the same information design and layout challenges as immersive VEs, but in addition, they may also be integrated with external windows or frames commonly used in desktop interfaces. This paper enumerates design approaches for the display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…This finding complies with prior research that showed that the more rich and/or less transparent is a computer-based learning environment the more insufficient it gets in promoting learning (e.g., Marshall and Young 2006). To overcome such a problem we need to develop and provide the students with tools that could inform them how rich and transparent is a webbased learning environment, as well as scaffolds that inform students how to handle the richness and transparency of its learning material (e.g., Polys and Bowman 2004;Swaak et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This finding complies with prior research that showed that the more rich and/or less transparent is a computer-based learning environment the more insufficient it gets in promoting learning (e.g., Marshall and Young 2006). To overcome such a problem we need to develop and provide the students with tools that could inform them how rich and transparent is a webbased learning environment, as well as scaffolds that inform students how to handle the richness and transparency of its learning material (e.g., Polys and Bowman 2004;Swaak et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Bowman et al have conducted extensive research on the advantages, challenges and best practices on hybrid 2D/3D visualization, proposing a taxonomy for Information-Rich Virtual Environments (IRVEs). In [16] the authors categorize visualizations depending on the physical and logical positioning of 2D and 3D displays, and in [17] they present a hybrid molecular visualization application for the CAVE system [18] that statically assigns 2D and 3D content to CAVE walls. CAVE2 is based on a cylindrical setup composed by 18 columns of 4 displays each.…”
Section: Related Workmentioning
confidence: 99%
“…In the jungle of new technologies today, one could easily add various other technologies for comparison, such as holobenches and PowerWalls [26], or also compare with the same technologies, but with varying components or features, e.g. with different projectors, interaction devices, varying network performance, or tracking technologies during the usage, or using other interaction techniques.…”
Section: Introductionmentioning
confidence: 99%